2020
DOI: 10.4028/www.scientific.net/kem.840.330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of White Mineral Trioxide Aggregate Using Precipitated Calcium Carbonate Extracted from Limestone

Abstract: White Mineral Trioxide Aggregate (WMTA) using precipitated CaCO3 (PCC) from limestone has been synthesized. PCC in calcite structure was extracted from limestone by calcination at 900 °C for 3 h, dissolved in 0.8 M nitric acid solution and followed with carbonation for 60 minutes. PCC was used for the synthesis of WMTA by mixing with tetraethoxyorthosilicate, bismuth oxide, aluminum oxide, catalyst of with HNO3 and NH3 solution and thermally treated at 1100 °C for 3 h. The products were characterized with Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Calcium carbonate from limestone and silica from rice husk ash were synthesized according to the procedures reported by Fa'izzah et.al. [4], and Ghadafi et.al. [5], respectively.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Calcium carbonate from limestone and silica from rice husk ash were synthesized according to the procedures reported by Fa'izzah et.al. [4], and Ghadafi et.al. [5], respectively.…”
Section: Methodsmentioning
confidence: 96%
“…This basic composition can be applied to a cement-like MTA synthesis from natural materials, such as limestone. Fa'izzah et al [4] and Ghadafi et al [5] reported a cement-like MTA synthesis using CaCO3 and SiO2 from limestone and rice husk ash, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…All of them are the C-O asymmetric stretching vibration of CO3. According to Faizzah [18], the absorption band characteristic of calcite phase PCC appears at wavenumbers 1420, 872, and 710 cm -1 .…”
Section: Figures 5 Xrd Pattern Of Pccmentioning
confidence: 99%
“…Deionized water (200 mL) was mixed with 200 μL of NH 3 25% as the catalyst and stirred at 500 rpm for 15 min. Then, 6.93 g of TEOS and 10.71 g of CaCO 3 were added and stirred for 30 min [14]. Al(NO 3 ) 3 0.74 g and 0.71 g SrCO 3 were added and stirred for 30 min.…”
Section: Synthesis Of Mta-sro and Mta-sro/hamentioning
confidence: 99%